Guiding the security protection of critical information infrastructure with scientific network security concept - Yangzhao LI; Changxiang SHEN; Nan TIAN (物联网学报)
In the current increasingly competitive international cyberspace security game,critical information infrastructure is facing a severe security situation.From the view of scientific principle,the essence of network security risk is the limitation of people’s cognitive logic of information science.It is impossible to build a solid network defense system,and it is not necessarily cost-effective from the view of economic benefits.In network security work,the most important thing is the convergence of security objectives.The key is to ensure that the logical combination of computing tasks is not tampered with or destroyed,and to achieve correct calculation.Focusing on this security goal,scientific and technological innovations were made in such aspects as logical correct verification theory,computing architecture and application mode of computing engineering.The problem that logical defects were not exploited by attackers was solved,a unity of offensive and defensive contradictions was formed,and the active immunity capability for information systems was established.